Meat quality attributes and physiological, metabolic and electroencephalographic responses to slaughter position and knife sharpness in cattle - Columbres, Imlan Jurhamid (2019)
This study was aimed at determining the effects of slaughtering methods on the welfare, physiological response and carcass and meat quality of cattle. To achieve this objective, the following experiments were conducted. In the first experiment, electroencephalographic changes, blood biochemistry and meat quality characteristics following upright and lateral recumbent slaughter position were assessed. Twenty Brahman cows were divided into two groups of 10 animals each and subjected to either upright slaughter position (UP) or lateral recumbent slaughter position (LP). Based on the EEG results, the changes in brain electrical activities were significantly different between animals slaughtered in an upright position (UP) and animals slaughtered in a lateral recumbent position (LP). Moreover, the results demonstrated that upright slaughter position caused hyperglycemia, lactic acidemia, and an increase in the levels of catecholamines and activities of liver enzymes. Slaughter positions affected electroencephalographic, physiological stress and blood biochemical responses in cattle. The second experiment compared the sharpness of the knife used in slaughter of cattle on physiological stress response, encephalographic changes and meat quality. Twenty Brahman cows were divided into two groups of 10 animals each and subjected to either sharp knife (SK) or less sharp knife (LSK) used in slaughter. Analysis of the sticking blood revealed that all variables (p<0.0001) were higher than their values in blood samples taken at pre-slaughter and post-slaughter. Following slaughter, the LSK animals had higher changes of electrical activity of the brain than that of pre-slaughter. Animals slaughtered in less sharp knife group (LSK) exhibited higher (p<0.0001) lactate, shear force, sarcomere length and myofibrillar fragmentation index than sharp knife group. The carbonyl and thiol contents determination revealed that the protein oxidation increased with aging time but was not affected by the slaughter knife. The catecholamines, glucose and liver enzymes were lower in animals slaughtered with a sharper knife. The present findings indicate that less sharp knife caused substantial physiological stress responses which compromises the animal welfare and meat quality. Likewise, the EEG profiles indicated that animals may have endured lesser amount of pain when being slaughtered using a sharp knife. Sharpness of the knife is very important factor to minimize the pain during slaughter.